2010
DOI: 10.1093/mutage/geq104
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the levels of PAH-DNA adducts in young adults living in Mexico City

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous components of polluted air. The Mexico City Metropolitan Area (MCMA), one of the most densely populated areas in the world, is 2240 m above sea level. At this altitude, less oxygen is available, making combustion less efficient and therefore producing more PAH pollutants. According to the Automatic Monitoring Network in Mexico City (RAMA, for its Spanish initials; http://www.sma.df.gob.mx/simat2/informaciontecnica/index.php?opcion=5&opciondifusion_bd=90), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Moreover, as PAHs have the potential to interfere with hormone systems, they can exert harmful effects on reproduction and immune function. As such, DNA damage induced by PAH exposure has been demonstrated by numerous authors (Garcia-Suastegui et al, 2011;Gunter et al, 2007;John et al, 2009). Long-term exposure to PAHs is suspected to raise the risks of cell damage via gene mutation and cardiopulmonary mortality (Kuo et al, 2003).…”
Section: Chronic or Long-term Health Effectsmentioning
confidence: 96%
“…Moreover, as PAHs have the potential to interfere with hormone systems, they can exert harmful effects on reproduction and immune function. As such, DNA damage induced by PAH exposure has been demonstrated by numerous authors (Garcia-Suastegui et al, 2011;Gunter et al, 2007;John et al, 2009). Long-term exposure to PAHs is suspected to raise the risks of cell damage via gene mutation and cardiopulmonary mortality (Kuo et al, 2003).…”
Section: Chronic or Long-term Health Effectsmentioning
confidence: 96%
“…As illustrated in figure 4, some studies found a higher frequency of CAs with exposure to heavy air pollution,50–56 others did not find statistically significant associations57 58 and others produced contradictory results 59…”
Section: Resultsmentioning
confidence: 99%
“…A significant relationship was found in long‐term cigarette smokers (28 ± 18 cigarettes per day for at least 40 years) who carry multiple at‐risk alleles. García‐Suástegui et al [] evaluated the levels of DNA damage in a population resident in Mexico City, Mexico, and a panel of at‐risk alleles of genes from activation and detoxification pathways. The levels of DNA adducts were significantly linked to the “sum of at‐risk alleles” in individuals heavily exposed to air pollutants.…”
Section: Dna Damage and Sum Of At‐risk Alleles In Environmentally‐expmentioning
confidence: 99%